A 'tissue model' to study the barrier effects of living tissues on the reactive species generated by surface air discharge. (18th April 2016) - He, Tongtong; Liu, Dingxin; Xu, Han; liu, Zhichao; Xu, Dehui; Li, Dong; Li, Qiaosong; Rong, Mingzhe; Kong, Michael G
Abstract: Gelatin gels are used as surrogates of human tissues to study their barrier effects on incoming reactive oxygen and nitrogen species (RONS) generated by surface air discharge. The penetration depth of nitrite into gelatin gel is measured in real time during plasma treatment, and the permeabilities of nitrite, nitrate, O3 and H2 O2 through gelatin gel films are quantified by measuring their concentrations in the water underneath such films after plasma treatment. It is found that the penetration speed of nitrite increases linearly with the mass fraction of water in the gelatin gels, and the permeabilities of nitrite and O3 are comparably smaller than that for H2 O2 and nitrate due to differences in their chemistry in gelatin gels. These results provide a quantitative basis to estimate the penetration processes of RONS in human tissues, and they also confirm that the composition of RONS is strongly dependent on the tissue depth and the plasma treatment time. A small electric field of up to 20 V cm −1 can greatly reduce the barrier effects of the tissue model regardless of their directions, for which the underlying mechanism is unclear. However, the electric field force on the objective RONS should not be the dominant mechanism.